2016
DOI: 10.1016/j.chom.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Group B Streptococcus Degrades Cyclic-di-AMP to Modulate STING-Dependent Type I Interferon Production

Abstract: SUMMARY Induction of type I interferon in response to microbial pathogens depends on a conserved cGAS-STING signaling pathway. The presence of DNA in the cytoplasm activates cGAS, while STING is activated by cyclic dinucleotides (cdNs) produced by cGAS or from bacterial origins. Here, we show that Group B Streptococcus (GBS) induces IFN-β production almost exclusively through cGAS-STING-dependent recognition of bacterial DNA. However, we find that GBS expresses an ectonucleotidase, CdnP, which hydrolyzes extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
149
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(152 citation statements)
references
References 51 publications
(98 reference statements)
3
149
0
Order By: Relevance
“…In the present study, we confirmed that Ply treatment can damage mitochondrial membrane to induce mtDNA release, and then promote the expression of type I IFN, which agreed with a recent report indicating that exposure to Ply leads to mitochondrial damage in epithelial cells, as well as the release of mtDNA, and contributes to IL‐1β expression . In addition to mtDNA, the c‐di‐AMP of Group B Streptococcus and Chlamydia trachomatis can also activate STING signaling pathway and then mediated the expression of IFN‐β . S. pn has been reported to secrete c‐di‐AMP ; however, whether the c‐di‐AMP of S. pn is related to the IFN‐β expression has not been reported.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we confirmed that Ply treatment can damage mitochondrial membrane to induce mtDNA release, and then promote the expression of type I IFN, which agreed with a recent report indicating that exposure to Ply leads to mitochondrial damage in epithelial cells, as well as the release of mtDNA, and contributes to IL‐1β expression . In addition to mtDNA, the c‐di‐AMP of Group B Streptococcus and Chlamydia trachomatis can also activate STING signaling pathway and then mediated the expression of IFN‐β . S. pn has been reported to secrete c‐di‐AMP ; however, whether the c‐di‐AMP of S. pn is related to the IFN‐β expression has not been reported.…”
Section: Discussionsupporting
confidence: 92%
“…The immune response is mostly dependent on the TLR pathway upon macrophage exposure to heat-killed Group B Streptococcus whereas live bacteria elicit a cGAS-STING dependent pathway [7374]. Interestingly, Andrade et al showed that S. agalactiae can degrade c-di-AMP present outside the bacteria via a cell-wall anchored ectonucleotidase.…”
Section: Beyond Sensing Viruses: the Role For Sting During Bacterial mentioning
confidence: 99%
“…Strikingly, this ectonucleotidase has no action on mammalian cGAMP. This mechanism of self-degrading extracellular CDN avoids over activation of STING and promotes bacterial virulence [74]. Identification of related strategies by other pathogens would be of great interest.…”
Section: Beyond Sensing Viruses: the Role For Sting During Bacterial mentioning
confidence: 99%
“…Moreover, vIRF1 from Kaposi’s sarcoma-associated Herpesvirus (KSHV) also binds to STING, preventing the interaction between STING and TBK1 (Ma et al, 2015). CdnP, an ectonucleotidase encoded by group B streptococcus, degrades c-di-AMP secreted by bacteria, alleviating host immune responses (Andrade et al, 2016). Above findings suggest that microbes utilize a universal way to suppress cGAS activity through blocking STING activity either directly or indirectly.…”
Section: Innate Immune Responses Induced By Dna Sensorsmentioning
confidence: 99%